The kinematic profile of ventral swimming start: sex diversity - Daria Malgorzata Rudnik; Daria Malgorzata Rudnik; Marek Rejman; Joao Paulo Vilas-Boas; Joao Paulo Vilas-Boas (Frontiers in Physiology, 2023)
It has been suggested that sex distinctions in physiology may affect the swimming performance of each sex differently. Yet, sex-based performance dependency has not been taken into consideration by most of the researchers evaluating swimming start. Therefore, the purpose of this research was to determine the effect of sex heterogeneity on the spatiotemporal characteristics of swimming start by investigating the determinants of its performance. A total of fifty-two international-level swimmers (thirty females and twenty-two males) performed three repetitions of the kick-start up to the 15-m mark. During trials, data were collected using video cameras and instrumented starting block. To search for evidence of differences between the two groups, the one-way ANOVA was conducted. Pearson’s correlation coefficients were calculated between measurements widely used to describe overall starting performance and selected kinematical variables of swimming start. A sex effect was exposed for temporal variables describing all swimming start phases (p ≤ 0.015). Male swimmers, by spending less time during the push-off from the starting block (p = 0.002; ηp2 = 0.18), reaching higher take-off velocity (p < 0.001; ηp2 = 0.29), traveling longer distances during flight (p < 0.001; ηp2 = 0.40), and swimming faster in the water phase (p < 0.001; ηp2 = 0.40), took starting advantage over their female counterparts. Consequently, performance measures such as 5-m, 10-m, and 15-m start times indicated that male participants were faster than females (p < 0.001; ηp2 ≥ 0.40). Only in the group of male swimmers a significant correlation between variables describing overall starting performance (5-m, 10-m, and 15-m times), and variables commonly highlighted as starting performance determining factors (block phase duration, take-off horizontal velocity, and flight distance) was found. The current study shows that the spatiotemporal variables of swimming start, the relation between them as well as overall starting performance, vary by sex. Consequently, the requirement of sex factor and its heterogeneity effect should be included not only in detailed characteristics of separate variables but also in all approaches undertaken. Those findings seem to play a crucial role mainly in swimming start evaluations in post-pubertal age groups of swimmers.